METHODS OF OBTAINING HEAT FROM SOLAR CONCENTRATORS. - Sharibayev Nasir Yusupjanovich , Makhmudov Bekzod Mirzaakhmad ugli (Research Focus International Scientific Journal, 2025)
This article presents a comprehensive analysis of methods for extracting thermal energy from solar concentrators. It discusses various technological approaches including parabolic dish concentrators, parabolic Stirling systems, parabolic water-heating concentrators, parabolic trough collectors, and Fresnel lens concentrators that focus solar radiation to generate heat. Based on experimental results and mathematical models, the study examines strategies for enhancing the efficiency of solar concentrators, achieving energy savings, and evaluates the economic and environmental impacts of these technologies. The article offers innovative solutions for the effective use of solar energy in drying processes and industrial thermal systems.